Young children's naive thinking about the biological world - Inagaki, Kayoko, 1944- (Essays in developmental psychology., 2002)
Presents research on the topic of young children's naive biology, examining such theoretical issues as processes, conditions and mechanisms in conceptual development using the development of biological understanding as the target case.